PENERAPAN MEDIA BALOK UNTUK MENINGKATKAN KEMAMPUAN BELAJAR HURUF HIJAIYAH PADA KELOMPOK B3 PAUD SANDHY PUTRA TELKOM TERNATE - Sofia, Pipih; Taib, Bahran (EDUKASI, 2018)
This research came from a background of the need of using Playing Blocks method to increase children’s creativity in learning process at Kindergarten. This research had a purpose to know the use of playing blocks method in increasing the student hijaiyah learning capability at Group B TK Sandhy Putra Telkom Ternate.This research used the class room action research which was carried out Group B at TK. Sandhy Putra Telkom Ternate by 2 cycles. This research used qualitative approach to get data and analized by observation sheet, observation rating, teachers and students documentation.The research result showed that in the first cycle, the criteria of success rate reached 47,06% (10 students) from 28 students, meanwhile in the second cycle, the criteria of success rached 78,6% (22 students). Thus, it can be concluded that playing block improved the student hijaiyah learning capability.Keywords: Playing blocks media, hijaiyah, learning capability